2007
DOI: 10.1158/1078-0432.ccr-06-2303
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of SOCS 1 and SOCS3 Enhances Resistance to Ionizing Radiation in Glioblastoma Multiforme

Abstract: Purpose: The expression of suppressors of cytokine signaling 1 (SOCS1) and SOCS3 genes is dysregulated in several solid tumors, causing aberrant activation of cell growth and survival signaling pathways. In this study, we analyzed SOCS1 and SOCS3 gene expression in glioblastoma multiforme (GBM) and studied the role of each protein in GBM cell signaling and radiation resistance. Experimental Design: SOCS1and SOCS3 gene expression was analyzed in 10 GBM cell lines by reverse transcription-PCR and Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
92
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 64 publications
(30 reference statements)
9
92
0
1
Order By: Relevance
“…Our studies showed that human glioblastoma tissues expressed higher levels of SOCS-3 than did control brain tissues, and that SOCS-3 promoter activity and mRNA expression is inhibited by ectopic PIAS3 expression. 1 Moreover, constitutive expression of SOCS-3 in human glioblastoma tissues correlated with enhanced cell survival and radioresistance in vitro (105). This resistance was dependent on SOCS-3 expression, as evidenced by marked sensitivity to ionizing radiation in SOCS-3 Ă€/Ă€ mouse embryonic fibroblasts compared with wild-type mouse embryonic fibroblasts (105).…”
Section: Involvement Of Socs-3 In Gliomasmentioning
confidence: 96%
See 4 more Smart Citations
“…Our studies showed that human glioblastoma tissues expressed higher levels of SOCS-3 than did control brain tissues, and that SOCS-3 promoter activity and mRNA expression is inhibited by ectopic PIAS3 expression. 1 Moreover, constitutive expression of SOCS-3 in human glioblastoma tissues correlated with enhanced cell survival and radioresistance in vitro (105). This resistance was dependent on SOCS-3 expression, as evidenced by marked sensitivity to ionizing radiation in SOCS-3 Ă€/Ă€ mouse embryonic fibroblasts compared with wild-type mouse embryonic fibroblasts (105).…”
Section: Involvement Of Socs-3 In Gliomasmentioning
confidence: 96%
“…In contrast, elevated SOCS-3 expression was reported in human breast cancer and melanoma tissues, as well as in a subset of classic Hodgkin's lymphoma cell lines and primary lymphoma cells (98)(99)(100)(101)(102)(103)(104). In several studies, SOCS-3 promoted cell growth and proliferation in a number of cancers (100,103,105), and elevated levels of SOCS-3 were reported to confer a growth advantage to a melanoma cell line (103). Lymphoma cells with low levels of endogenous SOCS-3 expression succumbed to proliferation arrest whereas cells that endogenously expressed higher levels of SOCS-3 did not undergo arrest (100).…”
Section: Involvement Of Socs-3 In Gliomasmentioning
confidence: 98%
See 3 more Smart Citations